(untitled) (Vallis Aurea, 2023)
This paper provides an overview of the funding opportunities for projects in Bulgarian municipaliti-es from the European Regional Development Fund under Operational programme „Regional Deve-lopment” 2007-2013 and Operational programme „Regions in Growth” 2014-2020 in the context of the development of the local tourism potential. Besides being presented opportunities for suppor-ting the development of local tourism potential by European Regional Development Fund at natio-nal level, this work is focused on the possibilities to develop local tourism potential by EU funding following the example of the Burgas Municipality. A review of the implemented projects, funed under operational programmes, of the Burgas Municipality during the programming period 2007-2013 has been carried out. The European Regional Development Fund co-funded projects concer-ning the development of tourism are classified into several groups. Opportunities for ЕU funding projects in the current programming period 2014-2020 are revealed in the context of the deve-lopment of alternative forms of tourism. Besides the opportunities for supporting the deve-lopment of local potential by EU Funds at national level, this paper introduces also the possibilities to develop local tourism potential by EU funding following the example of the Burgas Municipality